PENGARUH PENAMBAHAN DAGING IKAN TERI (Stolephorus sp.) DENGAN KONSENTRASI YANG BERBEDA TERHADAP PROFIL HEDONIK BASRENG - B. As’urin; Sulastri; Junaidi (LPPM Universitas Gunung Rinjani, 2025)
This study aims to determine the effect of adding anchovy meat (Stolephorus sp.) with different concentrations on the hedonic profile of basreng. In this study, anchovy meat (Stolephorus sp.) was added with concentrations P1 (20 gr), P2 (40 gr) and P3 (60 gr), each treatment was repeated three times. The hedonic test was conducted by 29 semi-trained respondents. The results of the hedonic test were then analyzed using ANOVA to determine any significant differences between treatments, and continued with the DUNCAN test to determine which treatment had a significant effect. The hedonic profile of basreng with the addition of anchovy meat had a significant effect on the aroma and texture (crispyness) of basreng, while the color and taste did not provide a significant difference. Based on the results of the hedonic test, the selected basreng was a stick with the addition of 60 grams of anchovy meat with a preference level of 4.18, which means that it was liked in terms of aroma, color, taste and texture (overall).